IMPLEMENTASI POLA KOMUNIKASI ORANG TUA DAN ANAK DALAM KISAH KELUARGA NABI IBRAHIM MENURUT AL-QUR’AN SURAT ASH-SHAFFAT AYAT 100-102 DI DESA BENGLE MAJALAYA KARAWANG - Aini, Hurul; Sitika, Achmad Junaedi; Nurhasan (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
Communication patterns are actions carried out by humans to convey messages from one person to another that have the same meaning. This communication pattern is also included in the scope of the family, especially parents and children, so that parents and children can exchange thoughts, feelings and desires towards each other. family members with each other so that a sense of understanding and understanding arises. This research aims to determine the communication patterns of parents and children in the story of the Prophet Ibrahim's family. Communication patterns between parents and children according to the Al-Qur'an surah Ash-Shaffat verses 100-102. Implementation of communication patterns between parents and children in the family story of the Prophet Ibrahim according to the Al-Qur'an Surah Ash-Shaffat verses 100-102 in Bengle Majalaya Village, Karawang.This research uses a descriptive qualitative approach with data collection techniques in the form of literature study, observation, interviews and documentation. Data processing and analysis in this research used descriptive methods with a qualitative approach by Miles and Huberman consisting of data reduction, data presentation and drawing conclusions. The results of this research show that: the communication patterns of parents and children in the story of the Prophet Ibrahim's family include communication patterns, namely obedience to parents, patience and being polite and courteous in answering questions. The communication pattern between parents and children according to the Al-Qur'an surah Ash-Shaffat verses 100-102 is a form of interpersonal communication pattern carried out by the Prophet Ibrahim (father) and Ismail (son). Interpersonal communication is the process of sending and receiving messages between two people or a small group of people by causing instant effects and feedback. Meanwhile, the implementation of parent and child communication patterns in the story of the Prophet Ibrahim's family according to the Al-Qur'an Surah Ash-Shaffat verses 100-102 in Bengle Village Majalaya Karawang shows that the researcher used the implementation elements consisting of 5 (five), namely communicator, communicant , messages, communication channels, communication media, and communication effects.Keywords: Communication Patterns; Family; Prophet Ibrahim.